ANALISIS YURIDIS PEMUNGUTAN BEA PEROLEHAN HAK TANAH DAN BANGUNAN ATAS PERALIHAN HAK TANAH DENGAN HIBAH WASIAT STUDI DI KOTA MEDAN - LIRA APRIANA SARI NASUTION (PREMISE LAW JURNAL, 2016)
Levying on land and building acquisition is a tax levied on land and building acquisition. Since Law No 28/2009 on local taxes and local retribution was in effect, the levy on land and building acquisition has become local authority although it used to be the central government authority. Law No 20/2000 on the Levy on Land and Building Acquisition states that separation which causes the transfer of inheritance will be levied tax. The process of transferring should be accompanied by authentic deed which is used as the basis for registering the rights in the Land Office. A PPAT (official empowered to draw up land deeds) has to ask for the receipt of the Levy on Land and Building Acquisition before signing the deed. The problems of the research were as follows: how about legal domicile of the stakeholders in levying on Land and Building Acquisition related to legacy and how about the role of PPAT in drawing up a deed on the transfer legacy related to the implementation of levying land and building acquisition. The role of PPAT is acting as the First Gate, the first person who controls and carries out administrative order in order to increase the levying on land and building acquisition because he has to ask for the receipt of the levy on land and building acquisition. A PPAT also acts as the person who helps calculate tax figures since the system of levying land building acquisition is self assessment, the payment is always done by taxpayers and the levy is always done by Dispenda (Regional Revenues Service), Medan.